Application of Aqueous Two-Phase System in the Extraction of Invertase Enzyme from Potato Tubers Using PEG8000/Potassium Phosphate - Kadhim, Meaad; Hameed, Khalid; Mahood, Hameed (Al-Khwarizmi Engineering Journal, 2025)
An aqueous two-phase system (ATPS) is a clean alternative for traditional aqueous-organic solvent extraction systems. This technique has proven to be highly effective for extracting and separating mixtures of biomolecules. The present investigation involved the extraction of the invertase enzyme from potato tubers utilizing ATPS. The system applied was: Polyethylene glycol 8000 combined with dipotassium diphosphate (PEG8000/PPH). The study investigated the impact of five factors, namely temperature, PEG8000 concentration, dipotassium phosphate concentration, pH, and the addition of sodium chloride (NaCl) or magnesium sulphate (MgSO4) as a catalyst, on the recovery percentage (%Rec) and partition coefficient (KE) of the invertase of the invertase enzyme in ATPS over the study period. The system achieved a maximum recovery (%Rec) of 87.52% and a maximum partition coefficient (KE) of 7.01 at a temperature of 10°C, with a PEG8000 concentration of 1.5 g/10 ml, a dipotassium phosphate concentration of 2.4 g/10 ml, and a pH of 10. After the addition of neutral salts, the system achieved a maximum %Rec of 91.9% and a maximum KE of 11.34 under the same optimal conditions, and a concentration of MgSO4 of 1 g/10 ml.